Perancangan dan Implementasi Video Profile Jurusan Akuntansi di SMK Globe National Plus 2 Batam - Jimmy Pratama; Vicky Anggrianto (National Conference for Community Service Project (NaCosPro), 2023)
In the era where technological developments are growing rapidly, humans activity has been helped a lot. There are a lot of benefit from technological developments. One of them is social media. Social media makes it easier to spread information everywhere. One of the things that we can spread on the internet is video profile. SMK Globe National Plus 2 Batam faces a problem of not having a video profile that can become the self-identity of the school. The development of the video profile was carried out using the method Multimedia Development Life Cycle or for short MDLC. The output of this research is expected to make it easier for schools to introduce accounting majors and at the same time disseminate important information about these majors.